Manajemen Kelas dalam Meningkatkan Pembelajaran yang Efektif - Muhamad Asim; Nurfazri Nurfazri; Hari Subagio; Hilman Ruba'i; Kasman Eka Prasetia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The purpose of this study is to identify and describe classroom management to improve effective learning. The method used in this research is descriptive qualitative with data collection techniques using observation and documentation. After the data has been collected, it is classified, analyzed and conclusions are drawn. The results showed that the classroom management that had been carried out by the teacher included planning, organizing, directing and supervising so as to increase the effectiveness of learning, by creating a conducive learning environment, motivating 101students, varied learning methods and the teacher's work ethic that made learning effective and efficient.